Association of STOP-Bang Questionnaire as a Screening Tool for Sleep Apnea and Postoperative Complications: A Systematic Review and Bayesian Meta-analysis of Prospective and Retrospective Cohort Studies. (October 2017) - Nagappa, Mahesh; Patra, Jayadeep; Wong, Jean; Subramani, Yamini; Singh, Mandeep; Ho, George; Wong, David T.; Chung, Frances
Abstract : BACKGROUND: The risk of postoperative complications increases with undiagnosed obstructive sleep apnea (OSA). The high-risk OSA (HR-OSA) patients can be easily identified using the STOP-Bang screening tool. The aim of this systematic review and meta-analysis is to determine the association of postoperative complications in patients screened as HR-OSA versus low-risk OSA (LR-OSA). METHODS: The following data bases were searched from January 1, 2008, to October 31, 2016, to identify the eligible articles: Cochrane Central Register of Controlled Trials, MEDLINE, PubMed, Cochrane Databases of Systematic Reviews, Medline-in-Process & other nonindexed citations, Google Scholar, Embase, Web of Sciences and Scopus. The search included studies with adult surgical patients screened for OSA with STOP-Bang questionnaire that reported at least 1 cardiopulmonary or any other complication requiring intensive care unit admission as diagnosis of outcome. We used a Bayesian random-effects analysis to evaluate the existing evidence of STOP-Bang in relation to OSA and to assess the association of postoperative complications with the identified HR-OSA patients by study design and methodologies. RESULTS: This systematic review and meta-analysis was conducted using 10 cohort studies: 23, 609 patients (HR-OSA, 7877; LR-OSA, 15, 732). The pooled odds of perioperative complications were higher in the HR-OSA versus LR-OSA patients (odds ratio 3.93, 95% credible interval, 1.85–7.77, P = .003; 6.86% vs 4.62%). The length of hospital stay was longer in HR-OSA by 2 days when compared with LR-OSA (5.0 ± 4.2 vs 3.4 ± 2.8 days; mean difference 2.01; 95% credible interval, 0.77–3.24; P = .005). Meta-regression to adjust for baseline confounding factors and subgroup analysis did not materially change the results. CONCLUSIONS: This systematic review and meta-analysis suggests that HR-OSA is related with higher risk of postoperative adverse events and longer length of hospital stay when compared with LR-OSA patients. Our findings support the implementation of the STOP-Bang screening tool for perioperative risk stratification. Abstract : Supplemental Digital Content is available in the text.